Efecto del medio básico, carbón activado, ácido giberélico y calidad de luz en la germinación in vitro de Masdevallia auropurpurea Reich - Pedraza Manrique, Jaime (Revista Científica, 2006)
An efficient seed germination system was developed for Masdevallia auropurpurea Reich., an endemic and endangered orchid of the prairies of Bogotá, Colombia. The effects of four facts (Murashige and Skoog salts (1962); Knudson C salts (1946); and Hidro-Coljap® salts), activated charcoal (0 and 0.5 0/0(w/v)), gibberellic acid (0.0; 2.68 and 5.3711M), and four light qualities (white light, darkness, red light and f ar-red light) on asymbiotic germination of Masdevallia auropurpureaReich., f., were studied. The best germination percentage and germination time was obtained on agar solidified medium supplement with Hidro-Coljap® salts and 2.68 iaM gibberellic acid under red light with a photoperiod of 16 h. The addition of activated charcoal did not stimulate either germination or the development of Masdevallia auropurpurea seedlings. This study describes a single medium-based protocol able to achieve more than 330,000 seedlings within 40 wk, starting from a single capsule. This protocol is sufficient for both large-scale propagation and in vitro conservation of this threatened orchid.